Beneficial effects of coagulase‐negative Staphylococci on Staphylococcus aureus skin colonization. Issue 10 (24th May 2021) - Bier, Katharina; Schittek, Birgit
Abstract: Our skin is constantly exposed to a large number of pathogens while at the same time undergoing selective colonization by commensal microorganisms such as coagulase‐negative Staphylococci. Staphylococcus aureus, however, is a facultative pathogen that is usually absent from healthy skin but frequently colonizes the inflamed skin of atopic dermatitis patients, where it further promotes inflammation. Enhanced S. aureus skin colonization was shown to correlate with a loss of microbiome diversity indicating a role for skin commensals to shape pathogen colonization. Together, keratinocytes and immune cells in the skin need to discriminate commensals from pathogens and orchestrate subsequent immune reactions in response to colonizing microbes. However, the mechanisms how individual commensals cooperate with keratinocytes and the immune system of the skin to prevent pathogen colonization are barely understood. In this review, we discuss the current knowledge on the functional effects of coagulase‐negative staphylococci, the most frequently isolated skin commensals, on S. aureus skin colonization.